2011
DOI: 10.1128/jb.01192-10
|View full text |Cite
|
Sign up to set email alerts
|

Core and Panmetabolism in Escherichia coli

Abstract: Escherichia coli exhibits a wide range of lifestyles encompassing commensalism and various pathogenic behaviors which its highly dynamic genome contributes to develop. How environmental and host factors shape the genetic structure of E. coli strains remains, however, largely unknown. Following a previous study of E. coli genomic diversity, we investigated its diversity at the metabolic level by building and analyzing the genomescale metabolic networks of 29 E. coli strains (8 commensal and 21 pathogenic strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 51 publications
9
49
0
1
Order By: Relevance
“…In particular, traits associated with the assimilation of small organic carbon sources are highly phylogenetically dispersed. This result is consistent with observations of wide variation among the strains of E.coli, Acinetobacter, Vibrio, etc., in their ability to use particular carbon substrates (Sarma et al, 2004;Keymer et al, 2007;Vieira et al, 2011). Previous studies have identified other phylogenetically dispersed bacterial traits like nutrient acquisition (Martiny et al, 2006) and particle colonization (Hunt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, traits associated with the assimilation of small organic carbon sources are highly phylogenetically dispersed. This result is consistent with observations of wide variation among the strains of E.coli, Acinetobacter, Vibrio, etc., in their ability to use particular carbon substrates (Sarma et al, 2004;Keymer et al, 2007;Vieira et al, 2011). Previous studies have identified other phylogenetically dispersed bacterial traits like nutrient acquisition (Martiny et al, 2006) and particle colonization (Hunt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the rationale behind this observation is challenging, as our knowledge of the role of TAs in bacteria, especially chromosomal TAs, is controversial (Tsilibaris et al, 2007;Van Melderen, 2010;Wang & Wood, 2011;Yamaguchi & Inouye, 2011). Nevertheless, another feature may distinguish the B2 group from the other E. coli phylogroups, besides its ancestral position (Chaudhuri & Henderson, 2012), unique virulence properties (Johnson et al, 2001), distinct metabolic networks (Vieira et al, 2011), highest genetic diversity (Tenaillon et al, 2010), specialized host adaptation (Carlos et al, 2010) and potential subspecies status (Tenaillon et al, 2010). Therefore, we analysed our data in this context.…”
Section: Discussionmentioning
confidence: 99%
“…enterohaemorrhagic, enteroinvasive and enterotoxigenic E. coli pathovars, belong to groups A, B1 or D (Chaudhuri & Henderson, 2012). Furthermore, the E. coli phylogroups also differ with regard to growth rate (Gordon & Cowling, 2003;Walk et al, 2007;Carlos et al, 2010), genome size (Bergthorsson & Ochman, 1998), metabolic networks (Vieira et al, 2011) and antibiotic resistance profiles (Bukh et al, 2009). Therefore, we assumed the existence of a potential link between TAs and E. coli phylogeny, as these genetic elements are ubiquitous in E. coli genomes, and appear to be implicated in the cell physiology at various levels.…”
Section: Introductionmentioning
confidence: 99%
“…Genomics efforts have highlighted the relatively small core genome and the relatively large pan-genome within a species such as E. coli (193,348), so it is highly likely that some of the pan-genome differences will affect adaptive responses. Plasmids and prophages add further variability to genomic capabilities (see "External DNA, genetic exchange, phages, and plasmids" below).…”
Section: Importance Of the Genotype In Determining The Nature Of Adapmentioning
confidence: 99%